Implementasi Restorative Justice dalam Penyelesaian Perkara Tindak Pidana melalui Penerapan Qanun di Aceh - Aulia Saiful Hadi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Restorative justice is a development of the purpose of prosecution in general that focuses on criminal acts that occur. As the purpose of the prosecution in general, that focus on retaliation for actions carried out with the aim of providing a deterrent effect for the perpetrator. Meanwhile, the purpose of prosecution based on restorative justice is to emphasize the fulfillment of the rights of each party involved with criminal acts that occur, especially realizing a sense of justice in society. In this case, the existence of restorative justice is as a concept of recovery of the parties involved to return to the original condition or resemble the original situation before the occurrence of criminal acts in society. The concept of restorative justice directly involves the perpetrator, victim, and community in accommodating the needs of the relevant parties. The policy of the State Police of the Republic of Indonesia, in general, has fulfilled the concept of restorative justice as a whole, which focuses on restoring the rights of the relevant parties in realizing a harmonious community life as usual. Similarly, with the customary judiciary found in Aceh with the existence of Qanun Aceh has also accommodated the overall concept of restorative justice to the settlement of criminal cases in the community.